Studi Empiris Terhadap Perilaku Halal Certification dan Halal Awareness Generasi Z Muslim Yogyakarta (Studi Pada Cake and Patisserie Shop di Yogyakarta) - Putri, Kasih Kinanti Adi; Astuti, Budi (Universitas Hamzanwadi, 2025)
Muslim consumers in buying food products will certainly consider the halalness of the product. This study aims to identify the repeat purchasing behavior of Muslim consumers generation z through halal certificate variables and halal awareness. This study uses a quantitative approach, the sampling technique used is convenience sampling with a sample size of 230 people. Data collection techniques through online questionnaires. Research data were analyzed using PLS software with Structural Equation Model (SEM) modeling. The results of this study indicate that halal certificates have a significant effect on halal awareness, trust and repurchase interest. While trust has a significant effect on repurchase interest, and halal awareness is significant on repurchase interest. The contribution of this study lies in a deeper understanding of the factors that influence the repurchase interest of halal food products through halal certificates and halal awareness.